Mouse thymic virus (MTLV). A mammalian herpesvirus cytolytic for CD4+ (L3T4+) T lymphocytes (The Rockefeller University Press, 1989)
Mouse thymic virus (MTLV; ICTV designation murid herpesvirus 3) infects developing T lymphocytes of neonatal mice, causing thymic necrosis and acute immunosuppression. Infected animals shed virus indefinitely. In the present report, two-color flow cytometric analysis of T lymphocyte subpopulations defined by the markers CD4 (L3T4) and CD8 (Lyt-2) was used to determine whether MTLV was lytic for a specific thymocyte population. At peak necrosis (8-11 d after infection), numbers of CD4+8+ cells in the thymus were reduced by 80% or more as compared with controls, and CD4+8- cells were reduced by greater than 98%. The major survivors were CD4-8+ and CD4-8- lymphocytes. These data indicate that the CD4 bearing lymphocyte is a primary target for cytolysis during MTLV infection. Possible parallels between MTLV and a newly described lymphotropic human herpesvirus, human herpesvirus 6 (HHV-6/HBLV), are also suggested.